A critical review of policies and legislation protecting Tanzanian wetlands. Issue 12 (2nd December 2018) - Materu, Silvia Francis; Urban, Brigitte; Heise, Susanne
ABSTRACT: Introduction : The benefit of wetlands for reducing poverty depends on the effectiveness of governance systems that influence peoples' behaviour in the wise use of wetlands. Objectives : This article critically analyses the current poverty reduction strategies, agrarian policies and economic investments governing wetland usage, especially in Tanzania, with regard to their impact on sustainable Ramsar wetlands management. Methodology : It analyses the management structure, domestic policies and legal framework relating to the protection of wetlands in Tanzania in accordance to the wise use concept of the Ramsar Convention. Outco mes : Tanzanian legal provisions for wetland protection are uncoordinated and too limited in their coverage and scope to sufficiently address the destruction of wetland ecosystems. There is no comprehensive national legal framework to guide sustainable management of Ramsar wetlands in Tanzania as laid out by the Ramsar Convention, which the country ratified in the year 2000. Conclusion : Without a sound legislative and policy-making framework, Tanzanian wetlands and their diverse ecosystem services will continue to degenerate with current strategies of increasing agribusiness and other developmental projects or economic investments. This paper provides critical baseline information to inform decision makers to develop appropriate policy and laws, which promote the wise use of wetlands in Tanzania.